Domestic hydrogen acceptance in the UK: Public perceptions of energy and environmental issues - Gordon, Joel; Balta-Ozkan, Nazmiye; Nabavi, Seyed Ali (Cranfield University, 2022)
This file provides evidence on public perceptions of energy and environmental issues in the United Kingdom. Online focus groups were conducted (February - April 2022) to examine consumer attitudes towards domestic hydrogen technologies for home use (heating and cooking appliances). At the start of each focus groups, participants were asked to give their views about climate change and the environment, and to describe their current level of engagement with pro-environmental behaviours including energy consumption habits. A total of 38 individual responses were recorded (n=58).
Keywords: 'Environmental attitudes and concerns'; 'Renewable energy awareness'; 'Environmental policy perceptions'; 'Climate change justice'; 'Net-zero'